The relationship between clinical dishonesty and perceived clinical stress among nursing students in southeast of Iran - Foozieh Rafati; Behnaz Bagherian; Parvin Mangolian shahrbabaki; Zahra Imani Goghary (BMC, 2020)
Abstract Background Clinical dishonesty is a complex problem that threatens the health and safety of patients. This study aimed to investigate the relationship between clinical dishonesty and perceived clinical stress in nursing students. Method This cross-sectional correlational study was conducted on 395 nursing students from 4 nursing colleges. The data were collected using a demographic information questionnaire, Nursing Student's Perception of Clinical Stressors, and a 12-item researcher-made questionnaire to evaluate the frequency of clinical dishonesty in the previous semester, the frequency of witnessing dishonest behavior among peers, and the perceived severity of unethical behavior. Results In this study, 89.1% of the students stated that they had committed at least one dishonest clinical behavior in the previous semester. The frequency of clinical dishonesty was significantly correlated with the frequency of observing dishonesty among peers (r = 0.053, p<0.01), perceived severity of unethical behavior (r = − 0.4, p<0.01), and perceived stress of students in the clinical setting (r = 0.28, p<0.01). Moreover, there were significant differences in the frequency of clinical dishonesty by gender (p = 0.006), the interest in the field of study (p = 0.004), and academic year (p = 0.002). Conclusion The frequency of clinical dishonesty among nursing students is high and needs attention. Furthermore, considering the positive relationship between dishonesty and perceived clinical stress, it is essential to teach effective strategies to nursing students to empower them to cope with clinical stress.